(untitled) (Experimental biology, 2015)
The objective of this in vitro study is to explore the cytocompatibility properties of purified carbonized rice husk(CRH) with cardiomyocytes. Microscopic observation evidenced that CRH cause slight modification in cell shape and in cell count only after five days of culture. The effect of CRH bound to cells was tested by reseeding treated H9c2 cells. Cells from a CRH-treated sample showed an ability to proliferate at the small concentration of CRH. At the concentration of 0,1 mg/ml CRH-treated cell showed a limited proliferation, however overtime cells continued to grow and recovered in shape and number.